Unlocking the potential of tropical root crop biotechnology in east Africa by establishing a genetic transformation platform for local farmerpreferred cassava cultivars - Nyaboga, E.; Njiru, J.; Nguu, E.; Gruissem, W.; Vanderschuren, H.; Tripathi, L. (Frontiers Media, 2013)
CassavagenetictransformationcapacityisstillmostlyrestrictedtoadvancedlaboratoriesintheUSA,EuropeandChina;anditsimplementationandmaintenanceinAfricanlaboratorieshasremainedscarce.TheimpactoftransgenictechnologiesforgeneticimprovementofcassavawilldependlargelyonthetransferofsuchcapabilitiestoresearchersinAfrica,wherecassavahasanimportantsocioeconomicniche.Amajorconstrainttothedevelopmentofgenetictransformationtechnologiesforcassavaimprovementhasbeenthelackofanefficientandrobusttransformationandregenerationsystem.Despitethesuccessachievedingeneticmodificationoffewcassavacultivars,includingthemodelcultivar60444,transgeniccassavaproductionremainsdifficultforfarmer-preferredcultivars.Inthisstudy,aprotocolforcultivar60444developedatETHZurichwassuccessfullyimplementedandoptimizedtoestablishtransformationoffarmer-preferredcassavacultivarspopularineastAfrica.Theconditionsforproductionandproliferationoffriableembryogeniccalli(FEC)andAgrobacterium-mediatedtransformationwereoptimizedforthreeeastAfricanfarmer-preferredcultivars(Ebwanatereka,KibandamenoandSerere).Ourresultsdemonstratedtransformationefficienciesofabout14–22independenttransgeniclinesper100mgofFECforfarmer-preferredcultivarsincomparisonto28linesper100mgofthemodelcultivar60444.Thepresence,integrationandexpressionofthetransgeneswereconfirmedbyPCR,SouthernblotanalysisandhistochemicalGUSassay.ThisstudyreportstheestablishmentofacassavatransformationplatformatInternationalInstituteofTropicalAgriculture(IITA)hostedbyBioscienceseasternandcentralAfrica(BecA)hubinKenyaandprovidesthebasisfortransferringimportanttraitssuchasvirusresistanceandprolongedshelf-lifetofarmer-preferredcultivarsineastAfrica.Weanticipatethatsuchplatformwillalsobeinstrumentaltotransfertechnologiestonationalagriculturalresearchsystems(NARS)insub-SaharanAfrica.